The Influence of the Project Based Learning Model on the Procedural Text Production Skills of Class X Students of SMK Negeri 1 Batang Onang - Ariani, Evi (Lembaga Riset Mutiara Akbar, 2023)
This research aims at three things. First, describe the skill of producing procedure text for grade X Student of SMK Negeri 1 Batang Onang, before applying the Project Based Learning model. Secondly, describe the skill of producing procedure text for grade X Student of SMK Negeri 1 Batang Onang, applying the Project Based Learning. Third, analyze the effect of applying the Project Based Learning on the skills of producing procedure text for grade X Student of SMK Negeri 1 Batang Onang. There are four theories used in this research. (1) the skils producing procedure teks, (3) the application of Project Based Learning models to skills producing procedure texts. This type of research is quantitative research with descriptive analytical research method. The research design used was the one group pretest and posttest. There are three research procedures, namely pretest, treatment, and posttest. The population of this research is the X grade students of SMK Negeri 1 Batang Onang who are registered in the 2023 school year, and the sample of this study is the students of class X ATPH (Agribisnis Tanaman Pangan dan Holticultura), amounting to 15 students. Based on the results of data analysis and discussion, the following three things were concluded. First, the skills of producing procedure text for grade X ATPH.I students at SMK Negeri 1 Batang Onang before being applied to the Project Based Learning model are in